A History of NFL Preseason and Exhibition Games: 1986 to 2013 - Ford, Mark L. (Rowman & Littlefield Publishers, 2014)
For fans of professional football who thought they had read everything about the history of the game, Mark L. Ford breaks new ground with this account of the NFL preseason. Described as “test labs” by Ford, preseason games are a time for trying out new strategies, considering future rule changes, and implementing television coverage innovations. For thousands of players who vie for a spot in the league every summer, the preseason is also the defining moment where careers can be made or broken. A History of NFL Preseason and Exhibition Games: 1986 to 2013 is one of two books by Ford on professional football’s preseason. Along with its companion volume—which covers 1960 to 1985—these resources provide information on every NFL and AFL preseason game played since the AFL was launched in 1960. All the interesting events and people that were part of these summer battles are detailed, as well as the first outings for new teams, new rules, and new stars. Ford also includes amusing anecdotes and mishaps, such as a last-minute defeat in 2000 when a player tackled his own teammate. Along the way, Ford recounts key off-season developments that would transform professional football from a modest enterprise into a global monopoly with annual revenues and assets worth billions. A History of NFL Preseason and Exhibition Games is a unique and important reference for pro football fans and cultural historians alike.